EVALUASI PROGRAM PUPUK SUBSIDI TERHADAP PRODUKTIVITAS KERJA KELOMPOK TANI KELURAHAN BATU - Hasmi Hasmi; Andi Uceng; Azis Kalrah (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2021)
The purpose of this study was to determine the Evaluation of the Subsidized Fertilizer Program on the productivity of the Farmer Group's Work in Batu Village to determine the factors that influence the Evaluation of the Subsidized Fertilizer Program on the Work Productivity of the Farmer Group's 30 people, while the sampling used was total sampling, using quantitative descriptive research, and techniques. The collection is through observation, questionnaires, documentation, interviews, and literature study. The data analysis technique used is descriptive statistics, data quality test, using a frequency table. The results showed that the evaluation of the Subsidized Fertilizer Program on the productivity of the farmer groups in Batu was in the Good category with a percentage of 63%, and the factors that influenced the evaluation of the subsidized fertilizer program on the productivity of the farmer groups in Batu with an accumulated result of 71.4 % in the Good category.